2022
DOI: 10.3389/fpls.2022.1054924
|View full text |Cite
|
Sign up to set email alerts
|

Nickel toxicity alters growth patterns and induces oxidative stress response in sweetpotato

Abstract: Nickel (Ni) contaminated soil is a persistent risk to plant growth and production worldwide. Therefore, to explore the Ni toxicity levels in sweetpotato production areas, we investigated the influence of different Ni treatments (0, 7.5, 15, 30, and 60 mg L-1) for 15 days on phenotype, Ni uptake, relative water content, gas exchange, photosynthetic pigments, oxidative stress, osmolytes, antioxidants, and enzymes of sweetpotato plants. The results presented that Ni at higher levels (30 and 60 mg L-1) substantial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 65 publications
(140 reference statements)
0
7
0
Order By: Relevance
“…Total soluble sugars activity was also increased under Ni stress which is related to earlier studies. Kumar et al (2022) found that the soluble sugar contents were increased by 72.1% under Ni stress in sweet potato. Application of BC improved glycine betaine, total soluble protein and total soluble sugar content.…”
Section: Discussionmentioning
confidence: 94%
“…Total soluble sugars activity was also increased under Ni stress which is related to earlier studies. Kumar et al (2022) found that the soluble sugar contents were increased by 72.1% under Ni stress in sweet potato. Application of BC improved glycine betaine, total soluble protein and total soluble sugar content.…”
Section: Discussionmentioning
confidence: 94%
“…The chlorophyll (Chl) was determined by the soaking method ( Zulqarnain et al., 2021 ; Kumar et al., 2022 ). Weigh 0.1 g fresh leaves, add 20 mL of 95% ethanol for dark treatment until the leaves turn white, fix the volume to 25 mLwith 95% ethanol, measure the OD value under A665, A649 and A470, and calculate the chlorophyll pigmented content;…”
Section: Methodsmentioning
confidence: 99%
“…High levels of Ni and Zn can cause phytotoxicity by inhibiting growth and reducing relative water content. These two also affect various aspects of photosynthesis, pigmentation, osmolality, and enzyme activity, resulting in leaf chlorosis and necrosis [ 210 , 211 ]. In a 2-year field experiment, El-Saadony et al [ 212 ] investigated the efficacy of Si-NPs (2.5 and 5.0 mmol/L) spray on Phaseolus vulgaris grown in Ni-polluted soil.…”
Section: Impacts Of Nps On Plants Under Hm Toxicitymentioning
confidence: 99%